HABITUASI DIMENSI KARAKTER KEBHINEKAAN GLOBAL DAN KARAKTER GOTONG ROYONG PENGUATAN PROFIL PELAJAR PANCASILA DI KELAS IV SD NEGERI FONTEIN 1 KOTA KUPANG - Un Lala, Sofia Godeliva; Koa, Marni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research analyzes the habituation strategy of the character dimensions of global diversity and gotong royong character in strengthening the Pancasila Student Profile in grade IV of Fontein 1 State Elementary School in Kupang City. The main focus is to understand the learning strategies used as well as the supporting and inhibiting factors of the habituation process. The research method used is a qualitative case study with data collection techniques in the form of observation, interviews, and documentation studies. The results revealed that the habituation strategy applied was quite effective in improving the understanding and application of the values of global diversity and mutual cooperation, supported by the curriculum, active learning, appropriate learning media, and an inclusive learning environment. However, there are obstacles such as a lack of understanding of implementation outside the classroom and limited related learning materials.